Analisis Kemampuan Berfikir Kritis Siswa yang Bergaya Kognitif Reflektif dan Impulsif pada Pembelajaran Biologi melalui Model SQ3R (Survey, Question, Read, Review, Recite) dengan Media Kartu Bergambar - ARNIYAWATI ARNIYAWATI; IMAS CINTA MULYA (BIO-PEDAGOGI, 2017)
In the curriculum of 2013 critical thinking ability is a demand that must be implemented, but in reality the process of learning in the class has not been empowering students' critical thinking skills. Then besides critical thinking another aspect to note is the aspect of cognitive style. This study aims to determine the ability of critical thinking students’ cognitive reflective and impulsive style. The subjects of this study are the students of class VII A SMP Negeri 4 Tuban as many as 23 students, with 13 students with reflective cognitive style, and 10 students with cognitive impulsive style. Data collection technique in this research is MFFT (Matching Familiar Figures Test) developed by warli (2010) to know cognitive style and critical thinking test based on Ennis indicator (2011), then data about critical thinking of cognitive-style students Reflective and impulsive, was analyzed using nonparametric statistics through the Mann-Whitney test. The results in this study show the similarities between students who are reflective cognitive style with students who have cognitive impulsive style in students' critical thinking ability, because the result of the students in the same reflective style with impulsive students is because this subject is taken from the sample Class VII A where the class is the preferred class (superior). Thus it can be concluded that students' critical thinking ability with reflective cognitive style does not differ with cognitive impulsive students in Biology learning through SQ3R model (Survay, Question, Read, Recite, And Review) with pictorial card media.